The Mayo Clinic Hospital Mortality Reduction Project: Description and Results. Issue 2 (March 2020) - Mueller, Jeff T.; Thiemann, Kay M. B.; Lessow, Cynthia; Murad, M. Hassan; Wang, Zhen; Santrach, Paula; Poe, John
Abstract : EXECUTIVE SUMMARY: Quality improvement, regulatory, and payer organizations use various definitions of hospital mortality as clinical outcome measures. In this prospective study, the authors evaluated a multicomponent intervention aimed at reducing inpatient mortality in a multistate healthcare delivery system. The project was initiated because of a statistically nonsignificant upward trend in mortality suggested by a six-quarter rise in the observed/expected mortality ratio generated by the Vizient Clinical Data Base and Resource Manager. The design of the mortality reduction plan was influenced by the known limitations of using hospital-wide mortality as a quality improvement measure. The primary objective was to reduce mortality through focused care redesign. The project leadership team attempted to implement standardized system-wide improvements while allowing individual hospitals to simultaneously pursue site-specific practice redesign opportunities. Between Q3, 2015, and Q4, 2017, system-wide mortality reduced from 1.78 to 1.53 (per 100 admissions; p = .01). The actual plan implemented in Mayo Clinic's hospitals is included as Appendix A to this article, published online as Supplemental Digital Content. The authors included it to allow comparison with similar efforts at other healthcare systems, as well as to stimulate criticism and discussion by readers. Abstract : Supplemental Digital Content is available in the text